Perbedaan Frasa dalam Bahasa Al-Qur'an dan Bahasa Arab - Ilham, Muhammad Arifin; Maulani, Hikmah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to analyze the differences in phrases between the Koran and Arabic in linguistic and literary contexts. The method used is a comparative analysis of phrase structures in the two languages, by reviewing aspects of syntax, semantics and pragmatics. The research results show that although the Koranic language has the same roots as Arabic, its use has its own characteristics that reflect the beauty and excellence of the Koranic literature. There are 17 differences found between these two languages including the use of words, sentence patterns and language conventions that are unique to the language of the Koran. It is hoped that this research will provide a deeper understanding of the language of the Koran as well as contribute to the study of Arabic linguistics and literature in general.